Exploring Literacy Coach Research in Canada: A Review - Liu, Peng; Li, Xuyang; Ciren, Zhuoma (Language and Literacy / Langue et littératie, 2021)
The purpose of this review is to understand literacy coach research in Canada in order to facilitate further research in this regard. Research about literacy coaches in Canada remains at an initial stage, and there is no universally accepted definition of a “literacy coach.” Most literacy coach research in Canada has used a qualitative method. The research has shown that literacy coaches in Canada, who act as both guides and supporters in schools, also experience many challenges such as role confusion and inadequate time for carrying out their work. Scholars believe that setting up coaching models and collaboration may be ideal ways to deal with these problems. This review also found that the research has concentrated on literacy coaches in elementary and secondary schools in Ontario. This article concludes with implications and suggestions for future research about Canadian literacy coaches. More analysis about literacy coaches’ identity, their relationships with other stakeholders in the education system, and the challenges they face is needed in the Canadian context.